The relationship between sonographic parameters of brachial artery and smoking - A/L Ramanathan, Prahalad (2015)
Background Anatomical changes in brachial artery like thickening of initima-media thickness (IMT) has shown to significantly associated with progression of atherosclerosis. This changes will ultimately lead to manifestation of cardiac vascular disease like coronary artery disease and stroke, which causes 17.3 millions of death cases worldwide, in both developed and developing countries. The number of death cases will continue to increase if preventive measure is not taken to control the risk factors associated with the atherosclerosis. The high-resolution sonography has shown to be a non-invasive and radiation-free clinical tools in measuring IMT value of artery, which provide insight to the progression of atherosclerosis in high risk group including smokers. Aim and Objective The present study aimed to determine the association between sonography parameters of the brachial artery and smoking. Method High resolution ultrasonography was used to examine the brachial artery among smoker and non-smokers, which recruited from the staff of Hospital Universiti Sains Malaysia. The brachial artery is scanned in the antecubital fossa in a longitudinal fashion. Optimal brachial artery images were obtained at about 5-10 cm above the antecubital crease. This location was marked, and all subsequent images were obtained at the same location. The IMT at the far wall is measured directly as the distance between the lumen-intima and media-adventitia border at the distal portions of the brachial (5-10cm above elbow). Measurement of PSV and RI are taken. Doppler angle is keep at <60º. Result There were 45 staff of Hospital Universiti Sains Malaysia (HUSM) volunteered to participate in this study. Among these participants, 20 (44.4%) of them were smokers while 25 (55.6%) of them were non-smokers. The mean of the intimal media thickness is 0.36±0.01 mm for smokers and 0.30±0.01 mm for non-smokers. The mean of the peak systolic velocity is 57.50±14.79 cm/sec for smokers and 48.94±5.19 cm/sec for non-smokers. The mean of the resistive index is 0.90±0.03 for smokers and 0.85±0.13 for non-smokers. There is significant difference of brachial artery intimal media thickness and resistive index between smokers and non-smokers (p<0.01), but not the peak systolic value. Among the two significant variables, only intimal media thickness and duration of smoking showed significant correlation and regression (r=0.754; r2=0.568, p<0.01). Conclusion The present study revealed significant thickening of IMT in smokers compared to nonsmokers among HUSM staff. This suggested the application of high resolution ultrasonography in screening of IMT among smokers, which is consider as high risk group for atherosclerosis.